2019
DOI: 10.3390/rel11010019
|View full text |Cite
|
Sign up to set email alerts
|

Internet and Islamic Learning Practices in Indonesia: Social Media, Religious Populism, and Religious Authority

Abstract: Like in many other developing countries, Indonesia’s population has been amongst the most enthusiastic ‘uptakers’ of the internet, especially of social media. Most Indonesians utilize the internet as an information source, including religious ones. Various groups and communities of Islamic studies have appeared on social media along with religious leaders who are also active on social media. Based on the various characteristics that have emerged, Islamic learning practices scattered across various social media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 44 publications
0
29
0
2
Order By: Relevance
“…A positive or skeptical attitude towards the Web is determined by local cultural, political, or social factors (see e.g., Fukamizu 2007;Kawabata and Tamura 2007). For example, online Islam looks different in a multicultural country like Malaysia or Singapore than in the case of Arab countries or Islamic minorities (see e.g., Goalwin 2021;Mohamad 2018;Piela 2010;Ridwan et al 2019;Slama 2018;Solahudin and Fakhruroji 2020;Sorgenfrei 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A positive or skeptical attitude towards the Web is determined by local cultural, political, or social factors (see e.g., Fukamizu 2007;Kawabata and Tamura 2007). For example, online Islam looks different in a multicultural country like Malaysia or Singapore than in the case of Arab countries or Islamic minorities (see e.g., Goalwin 2021;Mohamad 2018;Piela 2010;Ridwan et al 2019;Slama 2018;Solahudin and Fakhruroji 2020;Sorgenfrei 2021).…”
Section: Discussionmentioning
confidence: 99%
“…They no longer rely on authorities although the sources they access may be authoritative. Researchers point out that in today's Western societies, the authority of the great religious traditions and church institutions has eroded (for discussion on this topic, see, e.g., Cloete 2016;Evolvi 2020;Giorgi 2019;Hutchings 2011Hutchings , 2017Kołodziejska 2018;Kołodziejska and Neumaier 2017;Porcu 2014;Solahudin and Fakhruroji 2020;Staehle 2020). On the other hand, some emphasize that the reverse process is taking place.…”
mentioning
confidence: 99%
“…A previous study showed that adolescents also used SM to seek oral health information (OHI) [ 11 ]. This may be especially relevant in Indonesia where it was reported that users spend more time on the internet than users in other parts of the world [ 12 ]. Thus, the internet may offer an opportunity to disseminate OHI targeting Indonesians adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…The growth of understanding and movement has spurred the emergence of various Islamic attitudes and characters. The scattered Islamic movements with several characters along with the technology development and social media show the phenomena of religious activity spirit in the wider community (Solahudin & Fakhruroji 2020).…”
Section: Introductionmentioning
confidence: 99%